Is Audit Quality at Risk in the Covid-19 Era? The Moderating Role of Client Complexity - Thalia, Michelle; Herusetya, Antonius (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2025)
This study investigated the association between low audit quality and the tendency to issue modified audit opinions (MAO), using the proxy of non-Big Four audit firms and non-industry-specialized auditors. It also investigated the moderating effect of client complexity on the relationship between audit quality and MAO, and examines the effect of COVID-19 pandemic on these relationships. The samples were all listed firms on the Indonesia Stock Exchange, except for financial industry over a period of 2018 2020 (1,020 firm-years observations). Using panel logistic regression analyses, this study reveals that non-Big Four audit firms have a greater tendency to issue MAO, with no association between non-industry-specialized auditors and the tendency to issue MAO. This study also identifies that client complexity represents a moderator that enhances the positive correlation between non-Big Four audit firms and MAO. Lastly, no evidence found of any difference in the audit quality between pre- and during COVID-19 pandemic.